FIGURATIVE AND ABSTRACT ASPECTS IN YEVGEN KRIP’S WORKS - Подлевський, С. В.; Пономаревська, О. І.; Гула, Є. П. (Art and Design, 2023)
Purpose: to investigate certain key thematic and stylistic aspects of the famous Ukrainian artist Yevhen Krip works in order to actualize interest to his art and regional artists, which should be included in the all-Ukrainian context of the history of national art formation at the turn of the 20th - 21st centuries. Methodology. The article is based on the comparativist and phenomenological methods, which are implemented by the way of studying the material and approaching the author and his works by using the phenomenological reduction. Results. The article raises the necessary issues of researching a wider spectrum of modern Ukrainian art in order to form a broader and thorough view of the history of its formation and development in the period between the turn of the 20th and 21st centuries. The key semiotic images in the work of the Chernihiv artist Yevgen Krip are briefly analyzed and their possible sources are suggested. The possibility of a specific author’s approach to the material, which was embodied through the reception of homage, is also considered. Scientific novelty consists in the first publication and analysis of the work of a previously little-studied author, which is key in understanding the development of art in the context of the Chernihiv art circle, and therefore in the formation of scientific interest in regional art centers in Ukraine. The key aspects of Yevhen Krip’s art are briefly reviewed, which affect a wide range of works of art: from the sacred to the suprematism. Practical significance. Results of the article can be introduced into the history of national art at the turn of the 20th - 21st centuries, and outline the regional features of the of Ukrainian art development in comparison to the dominant trends of the selected period of time. The basis of the article can serve as the beginning of the next more thorough study of the art of both the author and other artists from the Chernihiv.